National Perspective Plan for Women’s Education and National Policy on Education: Analyzing the Impact of Girls' Education and Women's Empowerment (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Girl's educational access and expansion demands not only increase enrolment but also remove to a large extent barriers to girls' equal educational opportunity. Along with this, the need to reach UEE's goal for all children requires proper implementation of laws and policies from the central to the grass root level with the right direction and efficiency to make them worthy of enjoyment. In this context, more research and deeper analysis of the root causes of the problems are equally significant in their implementation Education for women should not only produce good wives and mothers as anticipated in the past, but should also allow them to become career women as well as responsible citizens capable of independent decision making. National Education Policy -1986, Suggested Women's Education is equality, Educational institution encouraged to take action programmes for the better advancement of women. In addition to that, formal education will liberate women from the clutches of poverty , abuse of inequality and violence. A correlation matrix has been calculated to find the impact of inequality in education on various other parameters. In order to know the level of women empowerment in different parts of the world, variables such as female participation in national parliament, percentage of female literacy and participation rate of female labour-power were taken. To conclude observations the third and final part is given